(untitled) (Research, Society and Development, 2024)
The human papillomavirus (HPV) is associated with the development of cervical cancer, in which different factors may be associated with the persistence and progression of precancerous lesions, one of these factors being co-infections between HPV, Chlamydia trachomatis (CT) and Gardnerella vaginalis (GV). Thus, the objective of the work is to verify the incidence of HPV and CT and GV co-infections in women treated in a private laboratory in Aracaju, located in the state of Sergipe. The study is descriptive, cross-sectional and retrospective, analyzing the results of high-risk HPV genotyping tests, tomographic research and cytopathological examination, carried out between January and October 2022. During the study period, 1,312 women underwent vaginal secretion collection, with other high oncogenic risk HPV genotypes other than 16 and/or 18 being detected in 80.65% (296/367) of cases, followed by HPV-16 with 8.71% (32/367) and HPV- 18 with 3.82% (14 /367). Among patients infected with HPV, there were 30.7% (113/367) cases of co-infections, 14.16% (16/113) by CT and 81.42% (92/113) by GV, in addition to triple findings. infection, in 4.42% (5/113) of cases. Thus, it was observed that there was a higher incidence of HPV genotypes different from 16 and/or 18, in addition to cases of double and triple co-infections being found in women treated in the laboratory.